Electronic Banking Mechanisms and their Impact on Achieving Market Value: An Exploratory Study of a Number of Iraqi Private Banks. - Mohamed, Mohamed Fakhri; Ahmed, Hamed Khadir (Finance and Business Economies Review, 2019)
The study aimed at identifying the effect of electronic banking on achieving the market value of the bank. The study relied on the analytical descriptive method. The study used the questionnaire as a tool for collecting data and represents the study society in banks. A random sample of 100 employees was selected, The study found that the use of electronic banking is available in Iraqi banks at a very high level. It provides the requirements for the success of electronic banking in banks at a very high level, as well as the existence of a significant impact Machine mechanisms for statistical use of electronic banking to increase the market value of the bank, and the presence of a statistically significant effect of the availability of electronic banking requirements to increase the market value of the bank . The study recommended working on spreading e-banking awareness among customers and working to increase e-banking by focusing on e-banking marketing to target categories that do not care about electronic banking, as well as continuous updating of electronic banking services, studying the wishes and needs of customers and working towards achieving them. Success of electronic banking.